Country reports : the mediterranean regional project, Spain (Paris : Organisation for Economic Co-operation and Development, 1965)
The aim of the project was to survey the present educational system in each of the countries concerned; to asses long-term educational needs, particularly those relating to scientific and technical manpower, in the context of economic growth for the target year 1975 or thereabouts; and to formulate detailed plans, including financial estimates for meeting these needs.
OECD Education and Development
rpm 23/01/2019
Loans
Keywords: Education; Development; Spain